Optimizing Aviation MRO Content Marketing: A Case Study Using AHP and Generative AI for Content Idea Generation - Biglar, Elham; Palivela, Hemant (Global journal of Business and Integral Security, 2024)
This research is the first phase of a broader study, into the performance of GPT-4 as a Generative AI (GenAI) model in crafting specialized marketing content ideas, for the aviation Maintenance Repair and Overhaul (MRO). The study emphasizes three primary content types including short informative articles, case studies, and white papers. Using the Analytic Hierarchy Process (AHP), six industry experts evaluated the AI-generated content ideas based on their relevance to the industry, trendiness, and appropriateness for the content type. The findings revealed that GPT-4 was most effective at generating white paper ideas, with an effectiveness score of 93.13%, followed by short article ideas at 90.44% and case study ideas at 86.88%. The findings demonstrate how GenAI models, like GPT–4 can improve content marketing in sectors such, as aviation MRO where accurate and trustworthy information is essential. This study stands out for its use of GenAI, in the MRO industry showcasing proof of its ability to generate unique content ideas tailored to the sector setting the groundwork, for content development.